CONTEMPORARY PROBLEMS CONCERNING GRAVES IN THE VIEW OF THE QUR'AN AND SUNNAH - Ahmad Rasyid (Nida Al-Qur'an: Jurnal Pengkajian Islam, 2025)
Islam and its teachings are sourced from the Qur'an and Sunnah, all problems can be answered correctly according to the development of the times. One example of today's case is the issue of the demolition of graves because they did not pay levies to the local government. Also the problem of the Review of the Qur'an and Sunnah regarding graves because of the limited cemetery land in big cities, the graves of someone who has died, both pious and unpious people, the prophets, aulia, Kiyai such as raising graves, making grave markers with wooden tombstones or permanent tombstones made of stone, so that legal certainty is needed to answer these problems based on the guidance of the Qur'an and Sunnah. The method used is library research by collecting all information relevant to this discussion, so that a conclusion can be drawn on the problems faced by Muslims. The results of the review of the Qur'an and Sunnah in this article can be concluded as follows: 1. Review of the Qur'an and Sunnah: making grave markers with wooden headstones or permanent headstones from stones, laying just stones or tombstones (permissible) because they have a basis in Islam. This is due to efforts to mark the grave so that it is easy to recognize and easy to visit in the future. 2. Review of the Qur'an and Sunnah: installing a tombstone on top of the grave or providing a roof or house over it, namely: The grave may be raised just one inch so that it is recognized as a grave and is easier to visit, and also so that it is more respected by pilgrims. It is forbidden to put cement on graves and write on them and it is also forbidden to build buildings on graves.